ASUHAN KEPERAWATAN KELUARGA TAHAP PERKEMBANGAN REMAJA DENGAN INTERVENSI PEMBERIAN RENDAMAN KETUMBAR TERHADAP PENURUNAN NYERI HIPERKOLESTROLEMIA - Imas Permasi; Rina Puspita Sari; Hasan Basri (Yayasan Nusantara Hasana Berdikari, 2024)
Cholesterol is a fatty substance circulating in the blood, yellowish in color and shaped like wax, which is produced by the liver. The normal value for total cholesterol levels is ≤200 mg/dl, high cholesterol is 200-239 mg/dl, and very high cholesterol reaches ≥239 mg/dl (Prisilia Kurnia Wati, 2020). From conducting a case study, namely to describe nursing care for families with adolescent developmental stages with the intervention of providing coriander soaking to reduce hypercholesterolemia pain in Mr. B. The method used is a case study conducted on Mr. B for 10 days, by administering a coriander water soak to reduce hypercholesterolemia pain. After 10 days of intervention with coriander soaking, the hypercholesterolemia pain was reduced from a scale of 3 to 0. There was a reduction in cholesterol from 245 mg/dl down to 175 mg/dl. There is a reduction in hypercholesterolemia pain in Mr. B after the intervention of soaking coriander for 10 days.